2019
DOI: 10.1177/000313481908500332
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Incisional Hernia Repair: Complete Reconstruction of the Deficient Myofascial Component Using Christmas Tree Bone Anchors

Abstract: Lumbar incisional hernias are difficult to repair because one of the hernia margins is bone, namely, the iliac crest. Previous studies have described the use of orthopedic bone anchors that fix a mesh onto the iliac crest. We present a novel technique for open repair of large lumbar incisional hernias using a double-mesh technique in combination with suture-loaded bone anchors to reattach the abdominal wall musculature onto the iliac crest. The surgical technique involves creating a preperitoneal plane behind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Literature on this technique is scant. There are anecdotal reports describing fixation of the muscle by bone anchors ( 5 , 6 ). In the case presented, bone anchors were fixed to the iliac bone at an interval of one and a quarter inch starting from the anterior end of iliac crest to the posterior end.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature on this technique is scant. There are anecdotal reports describing fixation of the muscle by bone anchors ( 5 , 6 ). In the case presented, bone anchors were fixed to the iliac bone at an interval of one and a quarter inch starting from the anterior end of iliac crest to the posterior end.…”
Section: Discussionmentioning
confidence: 99%
“…Review of literature reveals hardly any reports of this technique being used for fixation of the mesh. There are anecdotal reports of bone anchors being used for fixing the muscles over the mesh ( 5 - 8 ). But this holds true only if there is adequate length of healthy muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Moreno-Egea et al published another study, also non-randomized, in which they made the same comparison and concluded that the laparoscopic approach was possible 12 . Baird-Gunning et al highlighted that fact that the minimally invasive option was not always the most adequate option for surgery, especially for major defects and those in which muscular atrophy was present 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly described alternative is the use of suture anchors. 43 , 44 , 48 , 49 One series of 8 patients, one of the largest series of this type, who received suture anchor fixation for flank hernias reported a recurrence rate of 20%. 49 Although our series is limited, our results compare favorably to this.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most technically difficult aspect of these hernia repairs is fixating the abdominal wall to the iliac crest when the blunt trauma “rips” the lateral 3 muscles off their origin. Methods described for this study include the use of bone anchors 43 , 44 , 48 , 49 and direct suture fixation. 50 The senior author has developed a method of hernia repair using 2-cm strips of macroporous polypropylene mesh 51 , 52 that are used as sutures.…”
Section: Introductionmentioning
confidence: 99%